Featherwing Beetles (Insecta: Coleoptera: Ptiliidae) - Henry S. Dybas (EDIS)
Featherwing beetles are the smallest known beetles, the majority of the species being a millimeter or less in length. The common name is derived from the distinctive structure of the wings which are believed to function primarily for passive flotation, as in the ciliate seeds of dandelions. These wings are normally folded out of sight under the wing covers or elytra, which in some genera are shortened and truncate. However, in preserved specimens the featherwings often project beyond the apex of the elytra and aid (together with the minute body size) in the recognition of this family. This document is EENY-177 (originally published as DPI Entomology Circular 218), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.